2016
DOI: 10.1371/journal.pone.0155355
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Antimicrobial Profiling of Propolis from Different Regions within Libya

Abstract: Extracts from twelve samples of propolis collected from different regions of Libya were tested for their activity against Trypanosoma brucei, Leishmania donovani, Plasmodium falciparum, Crithidia fasciculata and Mycobacterium marinum and the cytotoxicity of the extracts was tested against mammalian cells. All the extracts were active to some degree against all of the protozoa and the mycobacterium, exhibiting a range of EC50 values between 1.65 and 53.6 μg/ml. The toxicity against mammalian cell lines was only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 41 publications
7
56
0
Order By: Relevance
“…Different MIC values observed in experiments with the same strains of bacteria can be explained by different times and locations of sample collection. Such relationships have also been demonstrated in other studies [ 25 , 46 , 56 , 57 ]. As reported by us previously [ 25 ] and confirmed in our present study, among the samples evaluated, the extracts of red propolis exhibited the highest antimicrobial activity indicating a promising biological potential of this type of propolis [ 22 , 29 , 38 ].…”
Section: Resultssupporting
confidence: 85%
“…Different MIC values observed in experiments with the same strains of bacteria can be explained by different times and locations of sample collection. Such relationships have also been demonstrated in other studies [ 25 , 46 , 56 , 57 ]. As reported by us previously [ 25 ] and confirmed in our present study, among the samples evaluated, the extracts of red propolis exhibited the highest antimicrobial activity indicating a promising biological potential of this type of propolis [ 22 , 29 , 38 ].…”
Section: Resultssupporting
confidence: 85%
“…In Libya, propolis from Tukra and Al'Aquriyah, showed an important activity against Trypanosoma brucei, which is the aetiologic agent of sleeping sickness, and Leishmania donovani, which causes visceral leishmaniasis Trypanosoma brucei. [116] Later on, the authors, [114] supported the previous finding regarding antiparasitic activity of Libyan propolis: antitrypanosomal, antileishmanial, anti-Mycobacterium marinum, anti-Plasmodium falciparum and anti-Crithidia fasciculata.…”
Section: Northern African Coastsupporting
confidence: 71%
“…Phytochemical analysis of the Libyan propolis display the presence of compounds belonged to phenolic, flavonoids, terpenoids, phytosterols and coumarins. [114,115] Siheri et al [116] have isolated three diterpenes [13-epi-torulosal (37), acetyl-13-epi-cupressic acid (75) and 13-epi-cupressic acid (76)] ( Figure 4) from Libyan propolis with antiprotozoal effect.…”
Section: Levantine Coastmentioning
confidence: 99%
“…The content of 8-epi-helenalin compounds in this research, was the first reported to be found in propolis. While sesamin has been reported by Bankova V (2000) contained in Propolis of the Canary Islands.1 Then the content of curcumin in propolis has been reported by Li Yang (2013) who examines Chinese propolis.30 Then the compound kushenol F has been reported to be present in Libyan propolis by Siheri et al (2016). 31 …”
Section: Discussionmentioning
confidence: 98%